Pathogenicity of a microsporidium isolate from the diamondback moth against noctuid moths: characterization and implications for microbiological pest management - Abd Ghani, Idris; Dieng, Hamady; Abu Hassan, Zainal Abidin; Ramli, Norazsida; Kermani, Nadia; Satho, Tomomitsu; Ahmad, Hamdan; Abang, Fatimah; Fukumitsu, Yuki; Ahmad, Abu Hassan (The Public Library of Science (PLoS), 2013)
Background: Due to problems with chemical control, there is increasing interest in the use of microsporidia for control of lepidopteran pests. However, there have been few studies to evaluate the susceptibility of exotic species to microsporidia from indigenous Lepidoptera. Methodology/Principal Findings: We investigated some biological characteristics of the microsporidian parasite isolated from wild Plutella xylostella (PX) and evaluated its pathogenicity on the laboratory responses of sympatric invasive and resident noctuid moths. There were significant differences in spore size and morphology between PX and Spodoptera litura (SL) isolates. Spores of PX isolate were ovocylindrical, while those of SL were oval. PX spores were 1.05 times longer than those of SL, which in turn were 1.49 times wider than those of the PX. The timing of infection peaks was much shorter in SL and resulted in earlier larval death. There were no noticeable differences in amplicon size (two DNA fragments were each about 1200 base pairs in length). Phylogenetic analysis revealed that the small subunit (SSU) rRNA gene sequences of the two isolates shared a clade with Nosema/Vairimorpha sequences. The absence of octospores in infected spodopteran tissues suggested that PX and SL spores are closely related to Nosema plutellae and N. bombycis, respectively. Both SL and S. exigua (SE) exhibited susceptibility to the PX isolate infection, but showed different infection patterns. Tissular infection was more diverse in the former and resulted in much greater spore production and larval mortality. Microsporidium-infected larvae pupated among both infected and control larvae, but adult emergence occurred only in the second group. Conclusion/Significance: The PX isolate infection prevented completion of development of most leafworm and beet armyworm larvae. The ability of the microsporidian isolate to severely infect and kill larvae of both native and introduced spodopterans makes it a valuable candidate for biocontrol against lepidopteran pests.